- #1

- 427

- 2

Where n1 = refractive index of object space, n2 = refractive index of image space

R = Radius of curvature of the spherical surface

I tried to derive the expression but I got a different expression.

Let u and v be the object and image distance from the spherical surface respectively.

Suppose the spherical refracting surface produces the image of a real object placed at its first principal focus at infinity. Then,

u = +f1, v = infinity

For refraction at a spherical surface,

(n2)/v + (n1)/u = (n2 – n1)/R

(n2)/(infinity) + (n1)/f1 = (n2 – n1)/R

0 + (n1)/f1 = (n2 – n1)/R

f1 = [(n1)(R)]/( (n2 – n1)

Power = 1/f1

Therefore P = (n2 – n1)/[(n1)(R)]

Could you please tell me where I have gone wrong?